International perspectives on gender and higher education : student access and success - Fontanini, Christine; Joshi, K. M.; Paivandi, Saeed (Emerald Publishing Limited, 2020)
Despite improved access to higher education for women, the distribution of women and men varies considerably between different fields of study. The chapters in this edited collection explore the participation status of women in higher education across the varying socio-economic and sociological backgrounds observed in different countries and regions. Diving into the differing social and state intervention policies, individual motives of participation and additional gender inequalities including regional and ethnic disparities, this book offers readers a better understanding of the drivers of gendered trends in higher education, such as the evidently low presence of women in certain scientific and technical disciplines. The analysis focuses on the social construction of gender differences, as well as the roles played by the economy, culture, religion, legal background, and the internal dynamics of society. Ultimately, this book provides a comprehensive overview of recent developments concerning the presence of women in higher education in both developed and developing countries, resulting in a clear picture of the current situation, and how the future might look.
Includes index.
Keywords: Women in higher education.; Women -- Education (Higher); Feminism and education.; Discrimination in education.; Education -- Higher.; Higher & further education, tertiary education.; elektronické knihy; electronic books